Tales on co-response-ability in times of environmental polarization - Violeta Cabello (Ecology and Society)
In this paper I explore societal polarization as a challenge to environmental governance and sustainability transformations. I focus on how processes of knowledge co-production can be used as transformative avenues in highly polarized environmental disputes. I investigate the case of nonpoint driven eutrophication in the Mar Menor Lagoon, Spain, where the interplay of divergent epistemic, political, and affective processes exacerbates societal divisions around environmental degradation. Drawing on process-relational and affect theory, I argue that co-production within polarized contexts might focus on relational transformation by placing attention on how differences emerge from and are transformed within affective relations in knowledge encounters. Through a diffractive reading of a co-production experience with actors holding polarized positions in relation to the Mar Menor, the paper sheds light on the affective patterns underpinning polarization by framing, blaming, and eluding responsibility, which is termed the “responsibility trap.” It suggests that transcending “us vs them” dichotomies in environmental disputes calls for an affective engagement that shifts the responsibility trap to matters of co-response-ability. In our co-production experience, a partial relational transformation in this direction was achieved recognizing the lagoon as a shared matter of care, foregrounding how knowledge affects, embodying polarized narratives, exposing uncertainties in contested facts, and demonstrating that action can be taken even under uncertain conditions. Such a relational shift enabled a preliminary weaving of ways of knowing-feeling-becoming with the social-ecological transformation of the Mar Menor.